COVID-19 and the Research Community: Being vulnerable - Hunt, Jasper Elan (eLife, 2020)
Early-career researchers feel discouraged from exposing vulnerability even during a global crisis.
Keywords: COVID-19 and the Research Community; early-career researchers; mental health; careers in science; grad school